Optimalisasi Pengembangan Percaya Diri pada Anak Usia Dini - Masriani Masriani; Dina Liana (STAI Auliaurrasyidin Tembilahan, 2022)
Children who often receive and get disapproval, fear, and feel disappointment will cause children to lose their confidence. This will continually occur until they grow up if it consents. This will greatly interfere the children's development in many ways. What parents can do in developing children's self-confidence are that they should 1) appreciate whatever the children got, 2) wisely praise in order not to be arrogance, 3 wisely criticize without blaming, 4) support their abilities; never compare them with other children, 5) establish a harmonious relationship. Institutions for early childhood can optimize the development of students’ self-confidence by 1) Familiarizing self-confidence through independent aspects, 2) Familiarizing self-confidence through expressing ideas, and 3) implementing learning methods that aim to increase student's self-confidence.